PENGARUH BRAND AMBASSADOR, BRAND STORYTELLING, DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN PARFUM HMNS - Oktaviani; Rifqi Basyari Aziz; Rizky Akbar; Wiwin Indrawati4 (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
ABSTRACT With the increase in sales figures from HMNS perfumes, researchers conducted research aimed at finding out how influential brand ambassadors, brand storytelling, and eWOM are on purchasing decisions on a product. Researchers used a population and sample of Universitas Pelita Bangsa students to test the study. This type of research uses quantitative methods with the distribution of filled questionnaires. Researchers have 125 respondents whose data can be processed. In processing data results from the distribution of questionnaires, researchers use validity test methods, reliability tests, classical assumption tests, multiple linear analysis and hypothesis tests. The results of the research conducted were 1) the calculated value of the brand ambassador variable (X1) was greater than the ttable (2,506 > 1,979). 2) the calculated value of the brand storytelling variable (X2) is greater than the ttable (3.277 > 1.978). 3) the calculated value of the word of mouth electronic variable (X3) is greater than ttable (2.134 > 1.978). From these results, it can be concluded that the views of brand ambassadors, brand storytelling, and eWOM affect purchasing decisions. Keyword: Brand Ambassador, Brand Storytelling, eWOM, and Purchase Decision